Physico-Chemical Characterization and Environmental Implications of Jarosite Waste from Zinc Hydrometallurgical Processing - Akhtar, Vaseem; Kulhary, Dinesh (Asian Journal of Chemistry, 2025)
This study reports the physico-chemical properties and environmental implications of jarosite waste generated from the zinc hydrometallurgical processing. Jarosite waste samples from a major zinc processing facility were analyzed alongside soil samples from surrounding areas to assess the potential environmental impacts. Comprehensive characterization was performed using multiple analytical techniques including ICP-OES for major element analysis, ICP-MS for trace elements and heavy metals, FTIR spectroscopy, XRD and zeta potential measurements. Results revealed that the jarosite waste contains significantly increased concentrations of Fe2O3 (37.8-42.5%), SO3 (20.9-26.1%) and ZnO (6.1-7.7%), with concerning levels of heavy metals including Zn (52,084-59,979 mg/kg), Pb (5,938-8,612 mg/kg) and Cd (140-237 mg/kg). XRD analysis confirmed the predominance of jarosite minerals with secondary phases of iron oxides and quartz. FTIR spectroscopy identified the characteristic sulfate stretching vibrations (1080-1190 cm–1) and Fe-O bonds (510-630 cm–1). Zeta potential measurements demonstrated the highly acidic nature of jarosite waste with an isoelectric point at approximately pH 3.2, significantly lower than surrounding soils (pH 5.8). Statistical analysis revealed the strong positive correlations between heavy metal concentrations and sulfate content, suggesting co-precipitation mechanisms during jarosite formation. The extreme acidity (pH 2.6-3.3) and high electrical conductivity (3.57-4.58 mS/cm) of jarosite waste present substantial environmental risks through metal leaching and acid mine drainage. This study provides critical insights into jarosite waste characteristics that can inform improved waste management strategies, remediation approaches and potential resource recovery opportunities in zinc hydrometallurgical processing.